2016
DOI: 10.3346/jkms.2016.31.10.1650
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Lumbar Lordosis and Deficient Acetabular Coverage Are Risk Factors for Subchondral Insufficiency Fracture

Abstract: Subchondral insufficiency fracture (SIF) of the femoral head occurs in the elderly and recipients of organ transplantation. Osteoporosis and deficient lateral coverage of the acetabulum are known risk factors for SIF. There has been no study about relation between spinopelvic alignment and anterior acetabular coverage with SIF. We therefore asked whether a decrease of lumbar lordosis and a deficiency in the anterior acetabular coverage are risk factors. We investigated 37 patients with SIF. There were 33 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Some researchers [33] have suggested that posterior pelvic tilt may contribute to SIF. However, our research suggests that a 20°posterior pelvic tilt is associated with a mean stress value approximately 1.3-fold higher than normal.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers [33] have suggested that posterior pelvic tilt may contribute to SIF. However, our research suggests that a 20°posterior pelvic tilt is associated with a mean stress value approximately 1.3-fold higher than normal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they might have more frequent complications: dislocation, periprosthetic fracture, and component loosening, and the results after THA might be inferior compared to osteoarthritic patients [34][35][36][37] or osteoporotic patients [43][44][45] . One more concern is late anterior dislocation because SIFFH patients might have progressive kyphosis and excessive posterior pelvic tilt 4,8,46 . Nevertheless, there has been no study reporting the results of THA in SIFFH patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 No debe dejarse de lado la evaluación por imágenes de la columna, porque la cifosis lumbar degenerativa y otras alteraciones del balance espinopélvico podrían ser factores predisponentes. 17 Sin embargo, en el caso reportado, nuestra paciente no tenía alteraciones en el espinograma.…”
Section: Discussionunclassified